Much ado about nothing? The COVID-19 pandemic and the spread of populist discourse in Portugal - Moniz, J.; Brás, T.; Santana Pereira, J.; Belchior, A. M. (Análise Social, 2024)
The COVID-19 pandemic and its socioeconomic impacts led to fears that a kind of pandemic-fuelled populism could erupt in crisis-struck societies. Through a content analysis of parliamentary debates on issues dear to populists, we explore the impact of COVID-19 on the incidence of populist rhetoric in Portugal in different moments of the pandemic and by different political parties. Our results indicate that, despite an increase of people-centrism during the first COVID-19 wave, the pandemic globally decreased the prevalence of populist rhetoric, suggesting that parties’ adoption of populist frames under a crisis may be dependent on the nature of that crisis.